Atomic Plasma Grafting: Precise Control of Functional Groups on Ti3C2Tx MXene for Room Temperature Gas Sensors - Wang, Ying; Fu, Jimin; Xu, Jiangang; Hu, Haibo; Ho, Derek (ACS applied materials & interfaces, 2023)
Gas sensing properties of two-dimensional (2D) materials are derived from charge transfer between the analyte and surface functional groups. However, for sensing films consisting of 2D Ti3C2Tx MXene nanosheets, the precise control of surface functional groups for achieving optimal gas sensing performance and the associate mechanism are still far from well understood. Herein, we present a functional group engineering strategy based on plasma exposure for optimizing the gas sensing performance of Ti3C2Tx MXene. For performance assessment and sensing mechanism elucidation, we synthesize few-layered Ti3C2Tx MXene through liquid exfoliation and then graft functional groups via in situ plasma treatment. Functionalized Ti3C2Tx MXene with large amounts of -O functional groups shows NO2 sensing properties that are unprecedented among MXene-based gas sensors. Density functional theory (DFT) calculations reveal that -O functional groups are associated with increased NO2 adsorption energy, thereby enhancing charge transport. The -O functionalized Ti3C2Tx sensor shows a record-breaking response of 13.8% toward 10 ppm NO2, good selectivity, and long-term stability at room temperature. The proposed technique is also capable of improving selectivity, a well-known challenge in chemoresistive gas sensing. This work paves the way to the possibility of using plasma grafting for precise functionalization of MXene surfaces toward practical realization of electronic devices.Gas sensing properties of two-dimensional (2D) materials are derived from charge transfer between the analyte and surface functional groups. However, for sensing films consisting of 2D Ti3C2Tx MXene nanosheets, the precise control of surface functional groups for achieving optimal gas sensing performance and the associate mechanism are still far from well understood. Herein, we present a functional group engineering strategy based on plasma exposure for optimizing the gas sensing performance of Ti3C2Tx MXene. For performance assessment and sensing mechanism elucidation, we synthesize few-layered Ti3C2Tx MXene through liquid exfoliation and then graft functional groups via in situ plasma treatment. Functionalized Ti3C2Tx MXene with large amounts of -O functional groups shows NO2 sensing properties that are unprecedented among MXene-based gas sensors. Density functional theory (DFT) calculations reveal that -O functional groups are associated with increased NO2 adsorption energy, thereby enhancing charge transport. The -O functionalized Ti3C2Tx sensor shows a record-breaking response of 13.8% toward 10 ppm NO2, good selectivity, and long-term stability at room temperature. The proposed technique is also capable of improving selectivity, a well-known challenge in chemoresistive gas sensing. This work paves the way to the possibility of using plasma grafting for precise functionalization of MXene surfaces toward practical realization of electronic devices.